Defining affordable housing: a study of secondary and tertiary impacts to housing affordability in Habitat for Humanity clients - Isola, Andrew Charles IV (My University, 2025)
Housing affordability is an important topic in the United States. Many communities currently have both a shortage in housing stock and, more importantly, a shortage in affordable housing stock. Many proposed policy and practice solutions exist to ease the strain on communities caused by the lack of affordable housing. Many of the proposed solutions are economic in nature, either supply side or demand side. However, research suggests that factors that impact housing affordability are more than just economic in nature but are also social and environmental in nature. By studying Habitat for Humanity clients in the state of North Carolina, this paper defines the myriad social, environmental, and economic factors that impact housing affordability and models the interactions between these factors, residents, and communities. These factors can be ranked as primary, secondary, or tertiary impacts to housing affordability.
Keywords: Affordable housing; Housing; Habitat for Humanity; Affordable housing definition; Housing policy